Coronavirus disease 2019 (COVID-19) related stroke incidence: a case series - Prabaningtyas, Hanindia Riani; Hapsari, Maria Yosita Ayu; Putra, Stefanus Erdana; Hafizhan, Muhammad; Mirawati, Diah Kurnia; Budianto, Pepi; Subandi, Subandi; Danuaji, Rivan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Coronavirus disease 2019 (COVID-19) can cause systemic and respiratory symptoms. Acute respiratory distress syndrome (ARDS), anemia, acute heart injury, secondary infection, and stroke are the complications of COVID-19. Age, oxidative stress, endothelial dysfunction, inflammatory status, vascular risk factors, and hypoxemia are risk factors for stroke associated with COVID-19. In this case report, two cases of COVID-19 complicated by stroke and other thromboembolic diseases were discussed. Case 1: a 46-year-old man presented with right extremities weakness, dysarthria, cough, colds, chest pain radiating to left upper extremity. He was diagnosed with moderate COVID-19, with complication of embolic stroke and myocardial infarction. After administration of IV furosemid and recombinant tissue plasminogen activator (rTPA), his condition improved, and he was discharged from our facility. Case 2: a 54-year-old woman presented with a decreased level of consciousness, skin discoloration, tenderness on her left calf, cough, fever, and shortness of breath. She was diagnosed with moderate COVID-19 with a complication of thrombotic stoke and deep vein thrombosis (DVT). She was treated with rTPA, IV citicoline, and fondaparinux for 5 days. In conclusion, COVID-19 carries a risk of thromboembolic complication. COVID-19 patients have a higher risk of bleeding, therefore, medications, particularly anticoagulant, should be administered with more caution.